Comparative study of gut microbiota in wild and captive Malaysian Mahseer (Tor tambroides) - Samsudin, Anjas Asmara @ Ab Hadi; Mohd Ikhsan, Natrah Fatin; Suyub, Iswan Budy; Tan, Chun K.; Jaoi, Marilyn; Kaman, Nazrien (John Wiley & Sons, 2018)
Aims: The aim of this study was to identify and compare the gut microbial community of wild and captive Tor tambroides through 16S rDNA metagenetic sequencing followed by functions prediction. Methods and results: The library of 16S rDNA V3‐V4 hypervariable regions of gut microbiota was amplified and sequenced using Illumina MiSeq. The sequencing data were analyzed using Quantitative Insights into Microbial Ecology (QIIME) pipeline and Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt). The most abundant bacterial phyla in both wild and captive T. tambroides were Firmicutes, Proteobacteria, Fusobacteria and Bacteroidetes. Cetobacterium spp., Peptostreptococcaceae family, Bacteroides spp., Phosphate solubilizing bacteria PSB‐M‐3, and Vibrio spp. were five most abundant OTU in wild T. tambroides as compared to Cetobacterium spp., Citrobacter spp., Aeromonadaceae family, Peptostreptococcaceae family and Turicibacter spp. in captive T. tambroides. Conclusion: In this study, the specimens of the wild T. tambroides contain more diverse gut microbiota than of the captive ones. The results suggested that Cetobacterium spp. is one of the core microbiota in guts of T. tambroides. Besides, high abundant Bacteroides spp., Citrobacter spp., Turicibacter spp., and Bacillus spp. may provide important functions in T. tambroides guts. Significance and impact of the study: The results of this study provide significant information of T. tambroides gut microbiota for further understanding of their physi-ological functions including growth and disease resistance.